RELIGIOUS MODERATION AS A PSYCHOPATHOLOGICAL SHIELD: CLINICAL STRATEGIES FOR COUNTERING PSYCHOLOGICAL EXTREMISM - Iqbal Bafadal; Masnun; Humamurrizqi; Abdul Hadi Sukmana (Universitas Islam Negeri Mataram, 2026)
This research presents an academic synthesis of religious moderation (Wasatiyyah) as a preventive intervention against psychopathology, grounded in Muhammad U. Faruque's multidimensional self model. The normative foundation of Wasatiyyah is rooted in the concept of maqashid al-shariah as formulated by classical scholars, including Ibn 'Asyur in Maqashid al-Syari'ah al-Islamiyyah and Yusuf Al-Qaradawi in Al-Shahwah al-Islamiyyah, both of whom regard balance (wasath) as both the objective of the shariah and a principle for the protection of the soul (hifzh al-nafs). From the perspective of Islamic psychology, moderation is understood not merely as a sociopolitical compromise, but as a clinical necessity that can be operationalized through measurable psychological indicators, such as moderate religiosity scales, dogmatism scales (Rokeach, 1960), and the Religious Moderation Assessment (RMA), in order to maintain balance among the bio-physiological, cognitive, and spiritual dimensions of the human being. This analysis highlights that extremism arises from a “spectrum error,” in which the individual reduces the transcendent subjectivity of the “I” into a rigid and closed ideological object. By integrating Abu Zayd al-Balkhi's classical medical tradition in his work Masalih al-Abdan wa al-Anfus with the practice of Tajarrud (self-detachment) from the Sunni Sufi tradition, this research proposes a new framework for holistic mental health. The method employed is an analytical-critical literature review of primary sources in Islamic psychology and the philosophy of the soul. The findings show that the Wasatiyyah approach is clinically proven to protect human moral agency and to facilitate the attainment of Qalb Salim as the highest condition of mental health in the Islamic tradition. The implications of this research include recommendations for mental health practitioners and educators in Muslim communities to adopt the principle of moderation as a methodology for psychological intervention grounded in Islamic spiritual values.